The Influence of Professionalism and Spiritual Intelligence on IAKN Employee Performance Tarutung in 2023 - Duinerri Sianturi; Binur Panjaitan; Jungjungan Simorangkir (Formosa Journal of Science and Technology, 2023)
This research aims to analyze the influence of professionalism on employee performance, Spiritual Intelligence on Employee Performance, Professionalism and Spiritual Intelligence on Employee Performance. This research uses descriptive and inferential quantitative methods. The research population was all IAKN Tarutung employees, totaling 113 people with a sample of 40 people. The research instrument is a closed questionnaire, which was prepared by the researcher based on research variable indicators. The questionnaire trial was carried out on 30 IAKN employees who were not research samples, and was tested using validity and reliability tests. Thus Ha is accepted and Ho is rejected, it can be concluded that professionalism and spiritual intelligence influence the performance of IAKN Tarutung employees positively and significantly because they have been empirically tested. The implication is that if performance is to be improved, it can be done through professionalism and spiritual intelligence.